Postcolonial Directions in Education : volume 9 : issue 1 - Hickling Hudson, Anne; Mayo, Peter; Raykov, Milosh; Medel, Sonia; Mazawi, Andre Elias (University of Malta. Faculty of Education, 2020)
Table of contents: 1/ MEDEL, S., & MAZAWI, A. E. - Special issue : the (de)colonial pedagogical possibilities of film and film festivals (part 2) -- 2/ ATOUI, F. - Return, recollect, imagine : decolonizing images, reclaiming Palestine -- 3/ GLICK, S., & DEAN, A. - Learning to be “good enough” : Hollywood’s role in standardizing knowledge and the myth of meritocracy -- 4/ BASSAN, N. - Festivals of films, decolonial spaces, and public pedagogy : some preliminary reflections -- 5/ COLIN, C. - Cámara de Combate. Latin American film festival(s) as reflection-action -- 6/ CRAMMOND, S. - imagineNATIVE. On Screen Protocols & Pathways: A Media Production Guide to Working with First Nations, Metis and Inuit Communities, Cultures, Concepts & Stories [book review] -- 7/ SANTOS, A. - Women made visible: Feminist art and media in post-1968 Mexico City [book review]. peer-reviewed